Public Engagement with the #CampurLGBT Campaign as Portrayed by Malaysian Netizens’ Response - Noor Amirah Asraf; Puteri Sarah Hanim Mohamad Shaiful; Zulkifli Abd Latif; Shazleen Mohamed (Asian Journal of Media and Communication, 2019)
The purpose of this study is to examine public engagement with the hashtag #CampurLGBT campaign as portrayed by Malaysian netizens’ response on social media. This study applies AIDA model, consisting of four levels, namely attention, interest, desire, and action. Netizens’ response to the campaign, such as their comments, discussions, and even pictures posted under the hashtag #CampurLGBT are analyzed, in order to understand public engagement with the issue, also to determine how the campaign may influence their views on the LGBT lifestyle. This study finds that despite the campaign being successful in recruiting followers and supporters of the movement, the number of those supporting it is relatively small compared with those who are against it. Those who respond positively to the campaign are mostly members of the LGBT community itself, also urban Malaysian netizens who have been exposed to the LGBT culture through friends and family members. While the netizens who have shown their negative responses are mostly concerned with the practice of being prohibited in Islam, also with the negative health implications of the LGBT lifestyle. They feel attacked by the ‘negative messages’ of the campaign, and therefore need to do the counter campaign. They explicitly declare their negative desire towards the campaign, also take action to reject the campaign.Keywords: public engagement; AIDA model; #CampurLGBT; #TolakLGBT.